Ergonomic Assessment of Manual Material Handling Workers In The Semarang Tofu Industry Utilizing SNI 9011:2021 - -, Amalia; Kurniatie, Menik Dwi; Nugroho, Doni Satriyo; Wijaya, Dewa Kusuma (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 10 No 01 (2024): Volume 10 No 01 Tahun 2024, 2024)
In order to produce delectable, nutritious and affordable pricing, tofu products go through a labor-intensive manufacturing process that demands physical exertion and muscular vigor. In Indonesia, particularly in Semarang, Central Java, the tofu manufacturing process is still carried out manually, including the handling of raw soybeans and finished tofu, generally called Manual Material Handling (MMH). Among the tasks performed by MMH workers include lifting soybean, holding soybean extraction, lifting and carrying tofu barrels. Lifting loads range from 10 to 70 kg. The objective of this paper is to assess the degree of ergonomic risks and complains among MMH workers. The method used is quantitative analysis with a cross-sectional research design that refers to SNI 9011: 2021. Research methods to collect data include observations, interviews, and surveys. 80% of respondents complained of experiencing pain. Painful body parts with a high level of frequency and severity are located in the neck, right shoulder, upper back, lower back, arm, and right hand. A score of 9 indicates a high-risk level for MSD concerns. The total score of potential ergonomic risks is in the range of 11–19, with body scores vary from 2 and 8, material handling scores is 8. In order to reduce the risk of ergonomic hazards in MMH activities, risk control efforts are carried out by dividing the load into acceptable limits, lifting loads balance on both sides of the body. Providing assisting devices, such as ergonomic hand trolleys, can handle huge amounts with fewer frequent material handlings. Counseling is carried out for workers to help them because more aware and knowledgeable about how to conduct MMH activities safely.